Optical solitons for complex Ginzburg-Landau model in nonlinear optics - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi; Baleanu, Dumitru (Elsevier Gmbh, Urban & Fischer Verlag, 2018)
This paper studies the complex Ginzburg-Landau equation (CGLE) which models soliton propagation in the presence of detuning factor in nonlinear optics. Dark, bright, dark-singular and a new dark-bright optical soliton solutions to the model are derived using the sine-Gordon equation method (SGEM). Singular soliton solutions are also celebrated. The model is studied with Kerr law, quadratic-cubic law and parabolic laws nonlinear fibers. It is hoped that the results reported in this paper can enrich the nonlinear dynamical behaviors of the CGLE. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Sine-Gordon equation method; Complex Ginzburg-Landau equation; Optical solitons; Kerr law; Quadratic-cubic law; Parabolic law